The association of hospital prevention processes and patient risk factors with the risk of Clostridium difficile infection: a population-based cohort study. Issue 7 (24th April 2015) - Daneman, N; Guttmann, A; Wang, X; Ma, X; Gibson, D; Stukel, TA
Abstract : Background: Clostridium difficile is the most common cause of healthcare-acquired infection; the real-world impacts of some proposed C. difficile prevention processes are unknown. Methods: We conducted a population-based retrospective cohort study of all patients admitted to acute care hospitals between April 2011 and March 2012 in Ontario, Canada. Hospital prevention practices were determined by survey of infection control programmes; responses were linked to patient-level risk factors and C. difficile outcomes in Ontario administrative databases. Multivariable generalised estimating equation (GEE) regression models were used to assess the impact of selected understudied hospital prevention processes on the patient-level risk of C. difficile infection, accounting for patient risk factors, baseline C. difficile rates and structural hospital characteristics. Results: C. difficile infections complicated 2341 of 653 896 admissions (3.6 per 1000 admissions). Implementation of the selected C. difficile prevention practices was variable across the 159 hospitals with isolation of all patients at onset of diarrhoea reported by 43 (27%), auditing of antibiotic stewardship compliance by 26 (16%), auditing of cleaning practices by 115 (72%), on-site diagnostic testing by 74 (47%), vancomycin as first-line treatment by 24 (15%) and reporting rates to senior leadership by 52 (33%). None of these processes were associated with a significantly reduced risk of C. difficile after adjustment for baseline C. difficile rates, structural hospital characteristics and patient-level factors. Patient-level factors were strongly associated with C. difficile risk, including age, comorbidities, non-elective and medical admissions. Conclusions: In the largest study to date, selected hospital prevention strategies were not associated with a statistically significant reduction in patients' risk of C. difficile infection. These prevention strategies have either limited effectiveness or were ineffectively implemented during the study period.